A Bacterial Expression Platform for Production of Therapeutic Proteins Containing Human-like O-Linked Glycans. Issue 2 (21st February 2019) - Du, Ting; Buenbrazo, Nakita; Kell, Laura; Rahmani, Sadia; Sim, Lyann; Withers, Stephen G.; DeFrees, Shawn; Wakarchuk, Warren
Summary: We have developed an Escherichia coli strain for the in vivo production of O-glycosylated proteins. This was achieved using a dual plasmid approach: one encoding a therapeutic protein target, and a second encoding the enzymatic machinery required for O-glycosylation. The latter plasmid encodes human polypeptide N-acetylgalactosaminyl transferase as well as a β1, 3-galactosyl transferase and UDP-Glc(NAc)-4-epimerase, both from Campylobacter jejuni, and a disulfide bond isomerase of bacterial or human origin. The effectiveness of this two-plasmid synthetic operon system has been tested on three proteins with therapeutic potential: the native and an engineered version of the naturally O-glycosylated human interferon α-2b, as well as human growth hormone with one engineered site of glycosylation. Having established proof of principle for the addition of the core-1 glycan onto proteins, we are now developing this system as a platform for producing and modifying human protein therapeutics with more complex O-glycan structures in E . coli . Graphical Abstract: Highlights: Designed and expressed a synthetic core-1 O-glycan synthesis operon in E . coli Improved the O-glycosylation sequon through sequence manipulation Produced glycosylated, biologically active interferon-α2b Demonstrated a platform expression system for core-1 O-glycan addition Abstract : Du et al. describe a synthetic biology approach to producing mammalian-like O-glycans in bacteria. They demonstrate that this glycan can be produced on two examples of human therapeutic proteins. This demonstration of a platform technology for glycosylation has the potential to improve serum half-life of therapeutic proteins made in bacteria.